P-239 Embryonic quality assessment from microRNA profiling. (30th June 2022) - Almutlaq, A; Gonzalez, X; Odia, R; Sun, X; Naja, R; Serhal, P; SenGupta, S. B
Abstract: Study question: Does the microRNA expression profile in blastocysts change with different embryonic quality parameters? Summary answer: MicroRNA expression showed significant changes when aneuploidy was present, in day-6 compared to day-5 blastocysts and with different trophectoderm (TE) morphology grades. What is known already: MicroRNA (miRNA) is a gene expression regulatory mechanism used as a diagnostic marker for some conditions. Despite the great magnitude of studies investigating the miRNA role in implantation and pregnancy complications, limited work has been done to evaluate it as a potential marker for preimplantation embryo quality. With the accelerated changes in gene expression at early embryos, the miRNA profile is a potential indicator of embryo quality. This study investigates the blastocyst miRNA profile in relation to three quality parameters: aneuploidy, the day of blastocyst formation and morphology. Study design, size, duration: We collected 122 surplus embryos donated for research by 46 consenting couples from Centre for Reproductive and Genetic Health, London. All samples were ICSI derived blastocysts (day5/6) with PGT-A results. For aneuploidy status comparison, samples were categorized according to the number of chromosomes affected (single/multiple) and type of aneuploidy (gain/loss/partial), compared to euploid. The day of blastocyst development has (day5/day6) groups, and finally samples were compared based on TE morphology (excellent/good/fair). Participants/materials, setting, methods: Frozen human embryos were individually thawed and transferred to a lysis buffer. The miRNAs were extracted from each sample then sequenced by next generation sequencing (NGS) using miRNA Library Kit (QIAGEN) with NextSeqTM 500 (illumina). The differential expression analysis was conducted using DESeq2 via GeneGlobe (QIAGEN). We set the significance cut-offs to (-2> foldchange >2) and (<0.05 FDR p-value). For gene ontology and pathway annotation, we used miRTargetLink 2.0 and miRPathDB 2.0 platforms. Main results and the role of chance: Compared to the euploid blastocysts, all aneuploid categories, except the single chromosome aneuploidy, had significant differences in miRNA expression. Nine miRNAs were altered in the group with multiple aneuploidies, and one was highly upregulated in embryos with partial losses or gains. The majority of differentially expressed (DE) miRNAs in samples with whole chromosomal gain or loss were downregulated. Conversely, four miRNAs showed a significant increase in day-6 blastocysts compared to day-5. Morphology grade comparisons showed no differences between excellent and good TE; however, six miRNAs were significantly changed in fair TE compared to good. The frequently altered miRNAs in these comparisons were ( hsa-let-7c-5p, hsa-miR-206, hsa-miR-184 and hsa-miR-203a-3p ). Unsurprisingly, pathway annotation of the DE miRNAs showed an involvement of key biological processes, like apoptosis, cell-cycle and differentiation, signalling and gene expression regulation, in all groups. The pathways of note in aneuploid blastocysts included DNA damage response, intrinsic and extrinsic apoptotic signalling, and regulation of cell-cycle G1/S associated events. In blastocyst day5/day6 comparison, embryonic and organ development were the most involved pathways, while in TE morphology, kinase activity and phosphorylation along with apoptosis and DNA damage response were significant. Limitations, reasons for caution: Differential expression analysis based on inner cell mass (ICM) morphology and blastocyst expansion were not applicable due to the inadequate number of embryos per group; as all the samples collected were in excellent or good quality. Wider implications of the findings: Gene expression profiling of miRNAs in human blastocysts will potentially identify biomarkers predictive of implantation success. Trial registration number: not applicable